Assessing the resurgent irrigation development program of the Philippines: National irrigation systems component - Roberto Clemente; Arthur L. Fajardo; Vicente G. Ballaran; Julie Carl P. Ureta; Arman S. Baulita; Kristel Camille J. Tapire (Philippine Institute for Development Studies (PIDS), 2020)
This Project focused on the evaluation of National Irrigation Systems (NIS) in the Philippines which consisted of 22 NIS in Luzon and 17 NIS in Visayas and Mindanao and are represented by 151 Irrigators Associations (IAs). The overall objective is to evaluate the policy, programmatic, and institutional framework governing irrigation development and management for the main purpose of improving irrigation performance and productivity of irrigated lands. The methodological approach to meet the specific objectives consisted of data collection through site visits, field measurements, and Key Informant Interviews (KII) and Focus Group Discussions (FGDs). This Project focused on the evaluation of National Irrigation Systems (NIS) in the Philippines which consisted of 22 NIS in Luzon and 17 NIS in Visayas and Mindanao and are represented by 151 Irrigators Associations (IAs). The overall objective is to evaluate the policy, programmatic, and institutional framework governing irrigation development and management for the main purpose of improving irrigation performance and productivity of irrigated lands. The methodological approach to meet the specific objectives consisted of data collection through site visits, field measurements, and Key Informant Interviews (KII) and Focus Group Discussions (FGDs). Results showed that siltation problems exist in canals of almost all NIS cases, causing reduced flow capacities that deprived the downstream portion from adequate water supply, among others. To improve performance of irrigation systems, good watershed management is needed as a preventive approach to address siltation of water courses and thus enhance water supply distribution. The National irrigation Administration (NIA) should allocate realistic resources for operation and maintenance to improve efficiency in water allocation and distribution from upstream to downstream users.
Keywords: 330; irrigation; national irrigation systems; program assessment; Philippine Resurgent Irrigation Development Program; National irrigation Administration